2006
DOI: 10.1207/s15328015tlm1804_11
|View full text |Cite
|
Sign up to set email alerts
|

A New Oral Health Elective for Medical Students at the University of Washington

Abstract: We describe the elective including curriculum development, course evaluation results, and steps for implementing a successful oral health elective into medical education. We highlight interprofessional collaboration and constituency building among medical and dental faculty and administrators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 8 publications
0
40
0
7
Order By: Relevance
“…sicians, as evidenced by other studies (13)(14)(15). On the other hand, patients felt that they would be more careful about oral hygiene if they were informed.…”
Section: Research Design Andmentioning
confidence: 66%
“…sicians, as evidenced by other studies (13)(14)(15). On the other hand, patients felt that they would be more careful about oral hygiene if they were informed.…”
Section: Research Design Andmentioning
confidence: 66%
“…Five medical schools offered special study modules in oral health and oral cancer. Special study modules/electives have been shown to increase oral cancer awareness amongst medical students [27]; however, students with an interest in oral health/oral cancer are likely to self-select for these study modules. Oral cancer risk factors, symptoms, and clinical examination were taught by the majority of medical schools but the clinical changes associated with oral cancer were less comprehensively taught.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also describe how oral health topics can be integrated into the existing medical school curriculum, for example incorporating oral cancer screening into their introduction to clinical medicine module. Inter-professional teaching and assessment between medical and dental students has been also shown to be beneficial to both groups of students [27,39].…”
Section: Discussionmentioning
confidence: 99%
“…26,27 In 2004, the Josiah Macy Jr. Foundation examined oral health education and published a report highlighting a role for physicians in the identification and referral of patients with oral health problems. 28,29 In 2008 the American Association of Medical Colleges published oral health learning objectives.…”
Section: Changing Environmentmentioning
confidence: 99%